Estimation of Stress - Strength Reliability for Parallel Redundant System Via Burr of type X Distribution - Alwan, Mohammad I.; Karam, Nada S. (Iraqi Journal of Science, 2024)
Estimation for the reliability of a parallel redundant system with independent stress and strength Burr distribution (type ) probability density functions is considered. Estimation of the reliability parameters is conducted according to the non-Bayesian estimation methods, namely the maximum likelihood and shrinkage methods. The Bayesian estimation is also considered using the Jeffery and Gamma priors with squared error, quadratic and weighted loss functions. Finally, the reliability estimate is calculated and the best method for estimation for each case is given using the mean squared error criteria.